2023
DOI: 10.1111/pce.14666
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA397 regulates tolerance to drought and fungal infection by regulating lignin deposition in chickpea root

Abstract: Plants deposit lignin in the secondary cell wall as a common response to drought and pathogen attacks. Cell wall localised multicopper oxidase family enzymes LACCASES (LACs) catalyse the formation of monolignol radicals and facilitate lignin formation. We show an upregulation of the expression of several LAC genes and a downregulation of microRNA397 (CamiR397) in response to natural drought in chickpea roots. CamiR397 was found to target LAC4 and LAC17L out of twenty annotated LACs in chickpea. CamiR397 and it… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 92 publications
0
2
0
Order By: Relevance
“…Transient overexpression of miR7125 or repression of its target, CCR, in apple fruit decreased lignin deposition under light-induced conditions [117]. In chickpea, overexpressing CamiR397 decreased the transcript levels of its targets, LAC4 and LAC17L and lignin accumulation in the root xylem and reduced xylem wall thickness [118]. A similar role of miR397 was observed during stone cell development in pear fruit [119].…”
Section: Lignin Regulation At Thementioning
confidence: 52%
“…Transient overexpression of miR7125 or repression of its target, CCR, in apple fruit decreased lignin deposition under light-induced conditions [117]. In chickpea, overexpressing CamiR397 decreased the transcript levels of its targets, LAC4 and LAC17L and lignin accumulation in the root xylem and reduced xylem wall thickness [118]. A similar role of miR397 was observed during stone cell development in pear fruit [119].…”
Section: Lignin Regulation At Thementioning
confidence: 52%
“…We observed that the expression levels of 4CL (CA.PGAv.1.6.scaffold546.13) and CCoAOMT (CCoAOMTCA.PGAv.1.6.scaffold354.27) were up-regulated in KANG ( Figure 9 and Figure S2 ), which modulated the lignin content, implying they may influence the resistance of pepper to C. capsici . In the chickpea root, microRNA397 reportedly regulates the tolerance to drought and fungal infections by controlling lignin deposition [ 35 ]. Phytohormones play a critical role in plant responses to viral infections [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plants 2024, 13, 527 10 of 15 microRNA397 reportedly regulates the tolerance to drought and fungal infections by controlling lignin deposition [35]. Phytohormones play a critical role in plant responses to viral infections [36].…”
Section: Analysis Of Disease Resistance-related Pathwaysmentioning
confidence: 99%
“…Likewise, the altered accumulation of lignin in the plant SCW leads to different responses to drought. For instance, the microRNA CamiR397 in chickpea (Cicer arietinum) can target the transcripts of lignin biosynthesis genes, reducing plant sensitivity to drought and pathogen infection by decreasing deposition of lignin (Sharma et al 2023). Overexpression of PtoMYB170 in transgenic poplar leads to stronger ligni cation and thicker SCW in xylem (Xu et al 2017).…”
Section: Introductionmentioning
confidence: 99%